Monetary policy of the reserve bank of India (Bombay, 1964)
THE papers submitted for this session may be broadly classified into five groups. The majority of writers have confined themselves mainly to the general aspects of the working of the monetary policy pursued by the Reserve Bank of India during the last decade. A number of them have studied specific aspects of the monetary policy measures; for example, the working of the Bank Rate policy includ ing the recent innovation in the technique of that policy, and the selective credit control measures. To the third group belong those papers which have sought to assess the role and the importance of financial intermediaries in the Indian money market and the need or otherwise for an extension of the control of the Reserve Bank of India over these institutions. Two papers have raised a number of interesting issues regarding the relationship of debt management with monetary policy. Lastly, we have a paper which has attempted to examine the monetary implications of the Reserve Bank's policy in the field of agricultural credit.
Keywords: Monetary policy